System of Measures to Be Taken Against Diseases of Tomato Crop in Greenhouses - Kulmuminovna, Khalmuminova Gulchexra (American Journal of Biology and Natural Sciences, 2025)
When choosing varieties of tomatoes and other cruciferous vegetables for cultivation in open and protected areas, it is advisable to pay special attention to those that are resistant to the diseases most common in this area. The introduction of resistant varieties increases yields and allows you to reduce the cost of protective measures.